Influence of socio-cultural values on girl-child education in Yobe State, Nigeria - Ibrahim, Aisha Ningi (2016)
The research provides a qualitative explanation of the influence of socio-cultural values on girl-child education in Yobe State, which is regarded as the educationally disadvantaged state in Nigeria. The girl-child may not be so lucky to be educated due to certain socio-cultural values which put them at high risk of exploitation,and violation of their rights. Indeed, under such conditions of abuse and neglect, girlchild education has come to symbolize the reality of all forms of discrimination in Yobe State. Yet,they are expected to grow into the good mothers of tomorrow,even in the face of these disadvantages.The objectives explored the reasons responsible for girl-child involvement in street hawking, the effects of street hawking on girlchild education, and women's exclusion in the family decision regarding girl-child education, the research further examined the views of policymakers on implementation and achievement of girl-child education programme in Yobe State.The research design involved a qualitative approach using ethnographic methods which specifically focused on key informants as the street hawkers parents,and policymakers drawn from three Local Government Areas of the State.The data collection technique involves participant observations, interviews, and focus group discussions using semi-structured open-ended questions. Observational data were converted to field notes for data analysis. The raw data were analysed using transcriptions, sorting, and repeated readings that identified major themes.In essence,this research,utilized both primary and secondary data that produced a balanced presentation. Major findings were presented as themes and the reasons for their involvement in street hawking includes means of exposure to future husbands,peer group socialization,to accrue income for their wedding xpenses, to maintain their bodily aesthetic needs, and to augment the family income for ustainability.Challenges facing the girl-child while hawking includes exposure to all forms of abuse,lack of safety, and being left behind in basic literacy. Based on the findings,girl-child education programme has been plagued with a lack of proper implementation. It has identified that strengthening the existing universal basic education programme and integrating gender issues with sensitivity would inspire,informs, and influence policy adjustment and transformation, enhances the involvement of girl-child education in the state with a view to achieving parity.Thus,the importance of maintaining the deep-rooted socio-cultural values and the patriarchal structure has been a significant reason for girl-child lack of access to education in Yobe State.